ANYTHING BUT HUMAN RIGHTS: US POLICY TOWARDS CUBA UNDER HELMS-BURTON - Arturo López-Levy; Harlan S. Abrahams (International Journal of Cuban Studies, 2010)
This article analyses the Human Rights dimension of US policy through the case study of US policy toward Cuba and concludes that US policy toward Cuba is not designed to further Human Rights. The article evaluates US policy toward Cuba by comparing and contrasting it with the principal theories and international norms of Human Rights and Human Rights foreign policy (Donnelly, Forsythe, and Koh). It also compares US policy toward Cuba with some concrete cases of US policies in which Human Rights improvements occurred. In terms of methods and conceptions, the paper reviews the 'all-or-nothing' approach and priorities of the Cuban Liberty and Democratic Solidarity (Libertad) Act of 1996 (Helms-Burton law) and its implementation. The paper concludes that the Human Rights component of US policy toward Cuba is minimal at best. US policy toward Cuba was not conceived to improve Human Rights on the island but to appease domestic constituencies through an agenda of property claims and Cold War anticommunist symbolism.